Catalase Deactivation Increases Dermatophyte Sensitivity to ROS Sources - Sebastian Jusuf; Michael K. Mansour (Journal of Fungi, 2024)
As the leading cause of fungal skin infections around the globe, dermatophytes are responsible for a multitude of skin ailments, ranging from athlete’s foot to ringworm. Due to the combination of its growing prevalence and antifungal misuse, antifungal-resistant dermatophyte strains like Trichophyton indotineae have begun to emerge, posing a significant global health risk. The emergence of these resistant dermatophytes highlights a critical need to identify alternative methods of treating dermatophyte infections. In our study, we utilized a 405 nm LED to establish that blue light can effectively inactivate catalase within a variety of both susceptible and resistant dermatophytes. Through this catalase inactivation process, light-treated dermatophytes were found to exhibit increased sensitivity to reactive oxygen species (ROS)-producing agents, improving the performance of antimicrobial agents such as H2O2 and amphotericin B. Our findings further demonstrate that light-induced catalase inactivation can inhibit the formation and polarized growth of hyphae from dermatophytes, suppressing biomass formation. Thus, by increasing ROS sensitization and inhibiting hyphal development, catalase-deactivating blue light offers a potential non-invasive and non-drug-reliant method of managing dermatophyte infections, opening new avenues for the potential treatment of these common infections in conjunction with existing treatments.